1998
DOI: 10.1136/bmj.316.7142.1423
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistant tuberculosis in prisons in Azerbaijan: case study

Abstract: Objectives: To document the existence of drug resistance in a tuberculosis treatment programme that adheres strictly to the DOTS principles (directly observed treatment, short course) and to determine the extent of drug resistance in a prison setting in one of the republics of the former Soviet Union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 4 publications
0
23
1
2
Order By: Relevance
“…206 Studies later revealed that these patients were suffering from drug-resistant disease. 207,208 DOTS was adopted as the national strategy by the Ministry of Health in 2005, after which the country reported 100 percent coverage. Despite this coverage, treatment success rates among DOTS patients were quite low because of increasing drug resistance.…”
Section: Country Profile: Azerbaijanmentioning
confidence: 99%
“…206 Studies later revealed that these patients were suffering from drug-resistant disease. 207,208 DOTS was adopted as the national strategy by the Ministry of Health in 2005, after which the country reported 100 percent coverage. Despite this coverage, treatment success rates among DOTS patients were quite low because of increasing drug resistance.…”
Section: Country Profile: Azerbaijanmentioning
confidence: 99%
“…im Tomsk Oblast (Russland) von 6,5% (1998) auf 13,7% (2002). Eine besonders hohe Prävalenz der multiresistenten Tuberkulose findet sich vor allem bei osteuropäischen Gefängnisinsassen (Coninx, Pfyffer et al 1998). Da die tuberkuloseerkrankten Insassen häufig nicht vollständig kuriert entlassen werden, tragen diese erheblich zu der Weiterverbreitung von…”
Section: Abbildung 2: Prävalenz Der Mdr-tb Unter Neuen Fällen 1994 -2unclassified
“…At the same time, the average age of TB patients declined, reflecting high levels of recent transmission. From the 1990s onward, a growing number of studies reported the high burdens of TB, in particular MDR-TB, in prisoners in the former USSR Republics (Drobniewski 1995 ;Drobniewski et al 1996;Conninx et al 1998;Kimerling et al 1999;Aerts et al 2000). Although there is in recent year a tendency towards a reduction in TB incidence among prison inmates, a higher proportion of TB patients among prisoners have MDR strains than in patients outside prison.…”
Section: The Burden Of Tb In Prisonsmentioning
confidence: 99%